Fourth Revolution and the Bottom Four Billion: Making Technologies Work for the Poor - Kshetri, Nir (University of Michigan Press, 2023)
Products and services based on advanced technologies such as artificial intelligence and blockchain are normally considered to be for rich consumers in advanced countries. Fourth Revolution and the Bottom Four Billion demonstrates how marginalized and vulnerable groups with limited resources can also benefit from these technologies. Nir Kshetri suggests that the falling costs and the increased ease of developing and deploying applications based on these technologies are making them more accessible. He illustrates how key emerging technologies are transforming major industries and application areas such as healthcare and pandemic preparedness, agriculture, finance, banking, and insurance. The book also looks at how these transformations are affecting the lives of low-income people in low- and middle-income countries and highlights the areas needing regulatory attention to adequately protect marginalized and vulnerable groups from the abuse and misuse of these technologies. Kshetri discusses how various barriers such as the lack of data, low resource languages, underdeveloped technology infrastructures, lack of computing power and shortage of skill and talent have hindered the adoption of these technologies among marginalized and vulnerable groups. Fourth Revolution and the Bottom Four Billion suggests that it is the responsibility of diverse stakeholders—governments, NGOs, international development organizations, academic institutions, the private sector, and others—to ensure that marginal groups also benefit from these transformative innovations.